2011
DOI: 10.1016/j.jad.2010.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of participants in a perinatal depression early detection program

Abstract: Despite being offered treatment options, a substantial proportion of women who screened positive had poor long-term mental health and relationship outcomes. This paper discusses some of the implications for perinatal early detection and treatment programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 57 publications
5
55
0
1
Order By: Relevance
“…14,[33][34][35] Gjerdingen et al clearly stated the problems they experienced in referring postpartum women from primary care sites to mental health practices for SCID assessment and diagnosis even when management was returned to the primary care site. 36 In a broadly implemented program of screening and follow-up in Australia, only about 50% of women had even the initial step of postpartum depression screening.…”
Section: P Os T Pa R T U M Depr Es Sion Scr Eening a Nd M A Nagementmentioning
confidence: 99%
“…14,[33][34][35] Gjerdingen et al clearly stated the problems they experienced in referring postpartum women from primary care sites to mental health practices for SCID assessment and diagnosis even when management was returned to the primary care site. 36 In a broadly implemented program of screening and follow-up in Australia, only about 50% of women had even the initial step of postpartum depression screening.…”
Section: P Os T Pa R T U M Depr Es Sion Scr Eening a Nd M A Nagementmentioning
confidence: 99%
“…[2][3][4][5][6] Neither the United States Preventive Services Task Force nor the American College of Obstetrics and Gynecology has made recommendations regarding routine PPD screening. 7,8 The American Academy of Pediatrics, however, recommends universal screening in the early postpartum period and screening for parental depression at each well-child visit.…”
Section: Introductionmentioning
confidence: 99%
“…Although research in this area is just beginning in pediatrics, we can learn from maternal depression management systems in obstetrics and family medicine settings where numerous intervention studies have shown efficacy (41)(42)(43)(44)(45)(46)(47)(48)(49). These clinics vary in the types of providers they employ, from obstetricians to mother-only general practitioners to maternal-child clinics but all differ from the pediatric models in that the providers are already the women's providers (as opposed to her children's).…”
Section: Lessons In Maternal Depression Management To Be Learned Frommentioning
confidence: 99%